Afraid to travel after COVID-19? Self-protection, coping and resilience against pandemic ‘travel fear’ - Zheng, Danni; Luo, Qiuju; Ritchie, Brent W. (Tourism management (1982), 2021)
COVID-19 has generated an unprecedented level of public fear, likely impeding tourism industry recovery after the pandemic is over. This study explores what trigger the public's pandemic ‘travel fear’ and how people impose self-protection, coping and resilience related to travel. The study integrates theories including protection motivation theory, coping and resilience theories to address the research aim. Using a quota sampling, an online survey of 1208 respondents across mainland China was conducted. Results found that threat severity and susceptibility can cause ‘travel fear’, which leads to protection motivation and protective travel behaviors after the pandemic outbreak. Findings also revealed that ‘travel fear’ can evoke different coping strategies, which increases people's psychological resilience and adoption of cautious travel behaviors. Several strategies are provided on how to mitigate people's ‘travel fear’ and encourage travel in a post-COVID-19 world. •The antecedents and behavioral consequences of individuals' pandemic ‘travel fear’.•How people impose self-protection, coping and resilience toward post-pandemic travel.•‘Travel fear’ evokes coping strategies and increases psychological resilience.•Emotional factors affecting protection motivation and post-pandemic behaviors.